Health Risk Assessment of Pesticide Residue in Millet, Maize, Sorghum and Rice Cultivated in Wukari, Nigeria - Imbasire, Nuhu; Raphael, Odoh; Asabe, Magomya M.; Ogu, Odiba Emmanuel; Samaila, Danjuma; Tutuwa, Adamu Nashuka; Patience, Jonathan; Agbu, Tsoken Danji; Shingu, Jesse Polly (Asian Journal of Science, Technology, Engineering, and Art, 2025)
The widespread application of pesticides in agriculture has raised global concerns about the accumulation of chemical residues in staple food crops and their implications for human health. This study quantitatively assessed the health risks associated with pesticide residues in millet, sorghum, and rice cultivated in Wukari, Nigeria. Using a cross-sectional design, grain samples were systematically collected from local farms and analyzed through gas chromatography–mass spectrometry (GC-MS) to identify and quantify residual pesticides. Detected compounds included organophosphates, carbamates, and pyrethroids, with variable concentrations across crop types. Health risk assessments were conducted by calculating the Estimated Daily Intake (EDI), Hazard Quotient (HQ), and Health Risk Index (HRI) for each pesticide, and comparing these values with the Maximum Residue Limits (MRLs) established by international regulatory bodies such as the FAO/WHO Codex Alimentarius. The results indicated that multiple pesticide residues exceeded permissible thresholds, with HQ and HRI values surpassing 1 in several cases, suggesting potential non-carcinogenic health risks, especially for sensitive groups including children and pregnant women. These elevated values are likely attributable to the extensive and often unregulated use of pesticides during cultivation and post-harvest storage, leading to bioaccumulation in the grains. The findings underscore the urgent need for regulatory enforcement, public health surveillance, and farmer education to mitigate dietary exposure to hazardous residues in commonly consumed cereals.